Analysis of Performance-Related Factors Associated with the Completeness of Electronic Medical Record Entry Among Healthcare Workers - Hariansyah Hariansyah; Endah Labati Silapurna; Oski Illiandri; Syamsul Arifin; Ermina Istiqomah (Journal La Medihealtico, 2026)
The performance and satisfaction of healthcare workers are critical determinants of the completeness of Electronic Medical Records (EMR). However, in 2024, Sengayam Regional General Hospital achieved only 50% of the targeted 100% EMR completeness rate, indicating challenges related to staff understanding and a suboptimal quality assurance system. This study aimed to examine factors associated with EMR completion performance among healthcare workers at Sengayam Regional General Hospital. This observational analytical study employed a cross-sectional design. The study population consisted of 165 healthcare workers, of whom 116 were selected as samples using purposive sampling techniques. Data were collected using a structured questionnaire. EMR completion performance served as the dependent variable, while age, education level, knowledge, and domicile were treated as independent variables. Bivariate analysis was conducted using the chi-square test, followed by multivariate analysis using multiple logistic regression. The findings demonstrated significant associations between EMR completion performance and age (p = 0.028), education (p = 0.000), and knowledge (p = 0.002). No significant association was found between domicile and EMR completion performance (p = 0.140). Among all variables examined, knowledge exhibited the strongest association with EMR completion performance (Exp(B) = 15.995). EMR completion performance among healthcare workers was significantly associated with age, education, and knowledge, whereas domicile showed no significant relationship. Knowledge emerged as the most influential factor affecting the completeness of Electronic Medical Record entry.